The senses of humor : self and laughter in modern America - Wickberg, Daniel, 1960- (Cornell University Press, 2015)
"The expression "sense of humor" was first coined in the 1840s, and the idea that such a sense was a personality trait to be valued developed only in the 1870s. What is the relationship between medieval humoral medicine and this distinctively modern idea of the sense of humor? What has it meant in the past 125 years to declare that someone lacks a sense of humor? Why do modern Americans say it is a good thing not to take oneself seriously? How is the joke, as a twentieth-century quasi-literary form, different from the traditional folktale? Wickberg addresses these questions among others and in the process uses the history of ideas to throw new light on the way contemporary Americans think and speak about humor and laughter." "The context of Wickberg's analysis is Anglo-American; the specifically British meanings of humor and laughter from the sixteenth century forward provide the framework for understanding American cultural values in the nineteenth and twentieth centuries. The genealogy of the sense of humor is, like the study of keywords, an avenue into a significant aspect of the cultural history of modernity. Drawing on a wide range of sources and disciplinary perspectives, Wickberg's analysis challenges many of the prevailing views of modern American culture and suggests a new model for cultural historians."--Jacket